Enhanced winter and summer trend difference of Madden–Julian Oscillation intensity since 1871. (13th April 2020) - Wang, Ziyue; Li, Tim; Gao, Jianyun; Peng, Melinda
Abstract: Long‐term winter and summer Madden–Julian Oscillation (MJO) trends in the past 138 years (1871–2008) were examined using National Oceanic and Atmospheric Administration (NOAA) 20th Century Reanalysis V2c dataset. It is found that MJO shows a distinctive different trend between boreal winter and summer. While the MJO intensity in both boreal winter and summer has a rising trend, the winter trend is much greater than the summer trend. As a result, the winter–summer difference shows a significant increasing trend. The distinctive winter and summer trends are attributed to the difference of atmospheric background circulation (such as vertical velocity) and static stability responses to the global warming between boreal winter and summer over equatorial eastern Indian Ocean. In boreal winter, both the surface moistening and strengthened inter‐tropical convergence zone convection contribute to an increase of MJO activity. This is in contrast to boreal summer when a greater static stability and anomalous subsidence tend to offset the moistening effect, leading to a relatively weaker increase of the MJO activity. Abstract : Madden–Julian Oscillation (MJO) intensity with real‐time multi‐variate MJO index derived from NOAA 20th Century Reanalysis V2c shows that winter trend is much greater than the summer trend since 1871. The reason behind the winter and summer distinctive trend is primarily attributed to the difference of atmospheric circulation response to the global warming between boreal winter and summer.